2010
DOI: 10.1039/b922506d
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved gas-phase kinetic study of the germylene addition reaction, GeH2 + C2D2

Abstract: Time-resolved studies of germylene, GeH(2), generated by laser flash photolysis of 3,4-dimethyl-1-germacyclopent-3-ene, have been carried out to obtain rate coefficients for its bimolecular reaction with C(2)D(2). The reaction was studied in the gas phase, mainly at a total pressure of 1.3 kPa (in SF(6) bath gas) at five temperatures in the range 298-558 K. Pressure variation measurements over the range 0.13-13 kPa (SF(6)) at 298, 397 and 558 K revealed a small pressure dependence but only at 558 K. After corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The parent inorganic silylene SiH 2 is often touted as a key intermediate formed during the decomposition of SiH 4 into thin films of Si. , As shown in Scheme , SiH 2 can be generated as a transient species by the flash photolysis of PhSiH 3 , while photolysis of Me 2 SiH 2 and 1-chloro-1-silacyclopent-3-ene ( 738 ) yield MeSiH and ClSiH, respectively. , The reactivity of SiH 2 with small molecules, such as O 2 , H 2 O, HCl, CO 2 , MeC­(O)­H, Me 2 O, alkenes, , alkynes, N 2 (the H 2 Si·N 2 adduct is stable at 10 K), NO, or silanes (e.g., MeSiH 3 ), can lead to E–H bond insertion, oxidative addition, hydride migration, or Lewis acid–base adduct formation, depending on the nature of the substrate (Scheme ). Furthermore, SiH 2 also has been the subject of numerous computational investigations. Laser flash photolysis of germacyclopentenes at 193 nm (Scheme ) yields GeH 2 , either in the gas phase or solution, , and reactivity paths that mirror those exhibited by SiH 2 with small molecules have been observed. In related work, gas phase laser flash photolysis of 1,3,4-trimethyl­germacyclopent-3-ene ( 739 ) yields transient MeGeH (Scheme ), while passage of an electric discharge through H 3 GeCl vapor affords the reactive halogermylene HGeCl . The chemistry of SnH 2 is much less developed and access to this parent tetrelene is possible by passing an electric discharge through gaseous SnH 4 , which instigates H 2 loss .…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%
See 1 more Smart Citation
“…The parent inorganic silylene SiH 2 is often touted as a key intermediate formed during the decomposition of SiH 4 into thin films of Si. , As shown in Scheme , SiH 2 can be generated as a transient species by the flash photolysis of PhSiH 3 , while photolysis of Me 2 SiH 2 and 1-chloro-1-silacyclopent-3-ene ( 738 ) yield MeSiH and ClSiH, respectively. , The reactivity of SiH 2 with small molecules, such as O 2 , H 2 O, HCl, CO 2 , MeC­(O)­H, Me 2 O, alkenes, , alkynes, N 2 (the H 2 Si·N 2 adduct is stable at 10 K), NO, or silanes (e.g., MeSiH 3 ), can lead to E–H bond insertion, oxidative addition, hydride migration, or Lewis acid–base adduct formation, depending on the nature of the substrate (Scheme ). Furthermore, SiH 2 also has been the subject of numerous computational investigations. Laser flash photolysis of germacyclopentenes at 193 nm (Scheme ) yields GeH 2 , either in the gas phase or solution, , and reactivity paths that mirror those exhibited by SiH 2 with small molecules have been observed. In related work, gas phase laser flash photolysis of 1,3,4-trimethyl­germacyclopent-3-ene ( 739 ) yields transient MeGeH (Scheme ), while passage of an electric discharge through H 3 GeCl vapor affords the reactive halogermylene HGeCl . The chemistry of SnH 2 is much less developed and access to this parent tetrelene is possible by passing an electric discharge through gaseous SnH 4 , which instigates H 2 loss .…”
Section: Molecular Hydrides Of the Group 14 Metals (Silicon Germanium...mentioning
confidence: 99%
“…1177 Addition of H 2 to the distorted cubane cluster Ar Me6 4 Sn 8 (1004) in toluene at 60 °C led to loss of Sn metal and formation of the yellow tetrameric hydride cluster [Ar Me6 Sn(H)] 4 (1005) in low yield (eq 83) (Ar Me6 = 2,6-Mes 2 C 6 H 3 ); a 21 % isolated yield of [Ar Me6 Sn(H)] 4 (1005) was possible by treating [Ar Me6 Sn(μ-Cl)] 2 with DIBAL-H. 1178 In the mid 2010s, the Wesemann group initiated a comprehensive study of the base-induced dehydrocoupling of alkystannanes (e.g., Trip 2 SnH 2 , 1006). To begin, exposure of Trip 2 SnH 2 (1006) (1008); in these reactions, the NHC also served as a hydrogen acceptor, generating the dihydroaminal (MeCNEt) 2 CH 2 as a coproduct (Scheme 151). 1179 (1040), which rearranges into Ar iPr6 H 2 Ge-SnAr Me6 (1038) via sequential Sn to Ge 1,2-intramolecular hydride shifts, a process that is promoted by the increased strength of Ge−H bonds over Sn−H linkages.…”
Section: Synthesis and Stoichiometric Reactivity Of Molecular Tin Hyd...mentioning
confidence: 99%
“…Less is known about the behaviour of GeH 2 and so we report further studies in the present paper. As well as our investigations [12–32] other kinetic studies have been undertaken by the group of King and Lawrance [33–35] in the gas phase and also by the group of Leigh [36] in the liquid phase, mainly of organogermylenes, GeR 2 (R=Me, Ph). A recent study by the group of Kaiser [37] has reported on the generation and gas phase behaviour of methylgermylene.…”
Section: Introductionmentioning
confidence: 94%